Partial discharge characteristics of mineral oil immersed transformer compared with natural ester and palm oil immersed transformer under different periods of impregnation - Maneerot, Sakda; Pattanadech, Norasage (My University, 2020)
This paper represents the partial discharge (PD) characteristics of mineral oil immersed transformer compared with natural ester, and palm oil immersed transformer under different periods of impregnation. Three identical three-phase transformers with 22kV/400V 50 kVA rated were designed and constructed. The first transformer was fully filled with mineral oil. The second transformer was fully filled with natural ester (FR3), and the third transformer was fully filled with palm oil. The partial discharge at 1.1Urated of these transformers with various conditions, i.e., non-impregnated paper, impregnated paper with 3 hours, and 6 hours was investigated. The impregnation process was done with 65 oC liquid temperature and 5 mmbar pressure. From the test results, it can be concluded that PD characteristics of the mineral oil immersed transformer was obviously different compared with these of the natural oil (FR3) immersed transformer and the palm oil immersed transformer. Moreover, the impregnation impacted PD characteristics of the tested transformers, which were analyzed and reported in this paper.
Keywords: Mineral oil; Natural ester; Palm oil; Partial discharge